Analysis of mechanical behavior of 3D printed heterogeneous particle-polymer composites. (15th September 2019) - Joyee, Erina Baynojir; Lu, Lu; Pan, Yayue
Abstract: Additive manufacturing has emerged as a powerful tool for fabrication of heterogeneous particle-polymer composites with enhanced material properties. These synthetic particle-polymer composites are lightweight, tough and showcase remarkable fracture toughness. Yet there is still a big knowledge gap in engineering particle microstructure orientation and loading fraction, to achieve the desired stress-deformation behavior of particle-polymer composites. To close this knowledge gap, it is essential to study the fracture toughness and stress-deformation patterns. Hence, in this paper, we additively manufactured particle-polymer composites with varied particle chain distributions and particle loading fractions, and investigated the mechanical behaviors of those composites both experimentally and analytically. Additionally, we investigated the influence of layer thickness on the Young's modulus and breaking propagation paths of the 3D printed samples. It is observed that the breaking edges remain smooth for parts printed with a small layer thickness and becomes irregular with asymmetrical fractures as the layer thickness is bigger than a critical value. The Young's modulus predicted by Cox-Krenchel model show similar trends as in the experimental results and validates the feasibility of the models in guiding the design of particle distribution, orientation and concentration in heterogeneous particle-polymer composites. Yet a higher modulus is predicted when particle chains are aligned parallel to the force direction, while a much smaller modulus, as small as the modulus of pure polymer, is predicted when particle chains are aligned perpendicular to the force direction. The analytical results of S1-0 and S1-45 composites agree with the experimental results with a deviation of 5.5%. While the analytical results of S1-90 do not agree with the experimental results, mainly due to the weak interfacial bonding between particle chain and polymer in the 3D printed composites. Both analytical and experimental results show that the particle-polymer composites with high particle volume loading fraction and parallel particle chain orientation has the highest stiffness.